AMIODARONE INDUCED OXIDATIVE STRESS IN STRESS - VULNERABLE ORGANS OF ADULT MALE RATS - CHAKRABORTY, ARIJIT; MONDAL, CHIRANJIT; SINHA, SABYASACHI; MANDAL, JAGADIS; K CHANDRA, AMAR (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Amiodarone used as an antiarrhythmic agent bears a structural resemblance to thyroid hormones containing about one-third iodine by weight. The pro-oxidant potentialities of amiodarone induced changes were studied. Materials and Methods: Male adult Wister rats were divided into two groups of eight animals each, and amiodarone was supplemented orally for 30 days against control. The urinary iodine content of both the groups was measured. Animals were sacrificed after completion of treatment; investigated parameters were adrenal morphology and histology, adrenal Î”5 3Î² hydroxyl steroid dehydrogenase (HSD) and serum cortisol level. Superoxide dismutase (SOD), catalase and lipid peroxidation (LPO) level were assayed in the liver, kidney and testis along with their histology. Serum glutamic-oxaloacetic transaminase (SGOT) and glutamic-pyruvate transaminase (SGPT) were measured. Obtained results were interpreted against the control group of rats. Results: Urinary iodine level was high after the amiodarone exposure. Hypertrophied cortex with enhanced Î”5 3Î² HSD activity in adrenal caused elevated serum cortisol level. Amiodarone exposure had increased LPO level with a concomitant rise in catalase and SOD activities in liver, kidney and testis in comparison to control (p<0.001). Simultaneously kidney showed shrinkage of the glomerulus, in liver the area surrounding the central canal found disrupted and in the testis seminiferous tubules, and germ cells were disorganized in comparison to control. SGOT and SGPT level were found elevated in the treated group. Conclusion: Amiodarone exposure develops stress for the metabolism and deiodinization of amiodarone releasing excessive iodine in circulation that in turn generates reactive oxygen species and free radicals resulting cellular damage of stress vulnerable organs. Keywords: Amiodarone, Excess iodine, Hypertrophied adrenal, Cellular damage, Stress-vulnerable organs, Reactive oxygen species.